Dietary sodium, potassium, and cardiometabolic risk: A cross-sectional analysis of hypertension in U.S. adults from NHANES 2017–2018 - Xiao Luo; Xuan Zhang; Longfeng Ran; Zhuojun Kang; Xinyu Fu; Xin Mu (PLoS ONE, 2026)
Background The relationships between dietary sodium and potassium intake and hypertension remain controversial, with recent population-based analyses yielding inconsistent findings. This study aimed to evaluate the associations of sodium and potassium intake with hypertension among U.S. adults and to explore potential interactions with demographic and lifestyle factors. Methods We conducted a cross-sectional analysis using data from 5,569 adults aged ≥20 years in the NHANES 2017–2018 cycle. Dietary intake was assessed using 24-hour dietary recall. Hypertension was defined based on self-reported diagnosis. Multivariable logistic regression models were used to estimate adjusted odds ratios (ORs) and 95% confidence intervals (CIs). Restricted cubic spline models examined nonlinear trends, and subgroup analyses were stratified by sex, age, and BMI. Results No significant associations were found between sodium or potassium intake and the odds of hypertension after adjusting for covariates (OR ≈ 1.00, P > 0.05) and findings were consistent when including the Na/K ratio. Results remained stable across sensitivity models and spline analysis. A non-significant inverse trend was observed for dietary fiber intake. Subgroup analyses suggested slightly stronger associations among older adults and individuals with obesity, although interaction terms were not statistically significant. Conclusion In this nationally representative sample, sodium and potassium intake were not independently associated with hypertension risk. These findings highlight the complexity of diet–blood pressure relationships and the importance of considering broader dietary patterns and individual characteristics in hypertension prevention strategies.